Recombinant neuropeptide Y modulates neuroendocrine signaling, inflammation, antioxidant defense, and nitrite resistance in tilapia - Ziyan Liu; Ruyue Sun; Yang Yu; Jiaqi Li; Tiansheng Zhu; Meiqing Li; Caiyun Sun; Wensheng Li (Aquaculture, 2026)

Full-Length Transcriptome Analysis of the Pituitary of Pre-Matured and Artificially Matured Female Japanese Eel (Anguilla japonica) - Yu Gao; Jiangling Li; Zhenguang Feng; Mingxi Huang; Wen Li; Ruihan Xu; Ruoxue Chen; Yu Ban; Jingjie Liang; Yan Huang; Yangjie Xie; Jianchun Chen; et al. (Journal of Ocean University of China, 2026)

Establishment of a TaqMan qPCR assay for the rapid detection and quantification of Nocardia seriolae in aquaculture - Zexia Chen; Yang Yu; Tiansheng Zhu; Chaowei Song; Zijun Wang; Ziyan Liu; Ran Cai; Lei Luo; Xiangjun Miao; Wensheng Li; Caiyun Sun (Aquaculture, 2026)

Recombinant expression and identification of tilapia neuropeptide Y in Bacillus subtilis and its protective potential against ammonia stress - Ziyan Liu; Ruyue Sun; Yang Yu; Jiaqi Li; Tiansheng Zhu; Meiqing Li; Caiyun Sun; Wensheng Li (Aquaculture, 2026)

Nitrite exposure on gills of Oreochromis niloticus: structure change, immune response, and apoptosis - Chaowei Song; Tiansheng Zhu; Ran Cai; Yang Yu; Ziyan Liu; Jianing Yan; Yingying Lian; Jiaqi Li; Wensheng Li (Frontiers in Marine Science, 2025)
Nitrite is one of the most common pollutants in high-density aquaculture systems and has a potentially serious impact on the health of fish. The gill, as the organ directly in contact with the environment, performs several vital physiological functions, including gas exchange, osmotic pressure regulation, and mucosal immunity. Using a series of nitrite concentration gradients, we investigated the impact of nitrite on tilapia gills, with a focus on its immune responses. The results indicated that nitrite exposure could significantly increase the number of mucus cells and change the subtypes of chloride cells. Nitrite exposure significantly elevated serum catalase (CAT) activity and decreased superoxide dismutase (SOD) activity. After nitrite treatment, the expression of ion channel protein genes was markedly affected, with a substantial increase in Na + /Cl − cotransporter ( ncc ) expression. Inflammatory gene expression in the gill was also significantly altered. Both in vitro and in vivo experiments revealed that key genes in the IL-17 signaling pathway were considerably altered after nitrite exposure. Mitochondrial damage and apoptosis in the gill tissues were also found after nitrite exposure. In conclusion, nitrite exposure altered immune function and ion transport, especially the activation of the IL-17 signaling pathway, damage to mitochondrial structure, and apoptosis in the gill. This study enhances our understanding of the mechanisms underlying nitrite-induced damage to the gill.

A Novel Mitochondrial-Related Gene Signature for the Prediction of Prognosis and Therapeutic Efficacy in Lower-Grade Glioma - Jingyi Yang; Lei Shen; Jiabin Zhou; Ji Wu; Chuqiao Yue; Tiansheng Wang; Songshan Chai; Yuankun Cai; Dongyuan Xu; Yu Lei; Jingwei Zhao; Yixuan Zhou; et al. (Biochemical Genetics, 2025)

Soluble TREM2 ameliorates pathological phenotypes in ischemic stroke models via modulating neuronal and microglial functions - Yanfei Guan; Feng Gao; Bo Chen; Tiansheng Yu; Linxin Meng; Qingzhuang Chen; Xiaodan Xiao (Experimental Brain Research, 2025)

Efficient hydrogen generation from ammonia borane hydrolysis over alkynyl-polyvinyl-alcohols decorated silica nanosphere supported ruthenium nanocatalyst - Xinxin Zhang; Yu Zhang; Kangzhou Wang; Deshun Huang; Kuan-Guan Liu; Xinhua Gao; Jianli Zhang; Tiansheng Zhao; Jianyu Wei; Guozong Yue; Xiaojiao Yang (Fuel, 2025)

Molecular level simulation and analysis of removal of sulfur, nitrogen and carbon residue in residual oil hydrotreating process - Xinglong Qin; Ye Ji; Guangqing Cai; Tiansheng Wang; Yu Du; Guangyu Mu; Jian Zhang; Xuezhi Duan; Xin Pu; Xin Han; Lei Ye; Jichang Liu (Chemical Engineering Journal, 2025)

Mechanism of cadmium (Cd) enrichment in the soil of karst areas with high geochemical background in Southwest China - Bo Li; Kun Lin; Xu Liu; Xudong Ma; Xuezhen Li; Zhiliang Wu; Cheng Li; Tao Yu; Tiansheng Wu; Zhongfang Yang (Chemical Geology, 2025)

Metal ions-mediated concerted electron-proton transfer enables catalytic oxidation of phenolic contaminants by permanganate - Tiansheng Chen; Pin Xie; Yanghai Yu; Xiaoguang Duan; Yuankui Sun; Xiaohong Guan (Water Research, 2025)

Improved mapping of heavy metals in agricultural soils using machine learning augmented with spatial regionalization indices - Xudong Ma; Dong-Xing Guan; Chaosheng Zhang; Tao Yu; Cheng Li; Zhiliang Wu; Bo Li; Wenda Geng; Tiansheng Wu; Zhongfang Yang (Journal of Hazardous Materials, 2024)

The evolution of digitalization capabilities during strategic renewal: A case study based on the ecological restoration enterprise practice - Erxiu Hou; Tiansheng Zhang; Ximing Yin; Jin Chen; Yu Ding (Journal of Cleaner Production, 2024)

Spatially varying relationships of soil Se concentration and rice Se concentration in Guangxi, China: A geographically weighted regression approach - Bo Li; Xu Liu; Chaosheng Zhang; Tao Yu; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Lei Wang; Kun Lin; Xudong Ma; Xuezhen Li; Husheng Zhang; et al. (Chemosphere, 2023)

Unraveling the intrinsic mechanism behind the selective oxidation of sulfonamide antibiotics in the Mn(II)/periodate process: The overlooked surface-mediated electron transfer process - Yanghai Yu; Hongyu Dong; Tiansheng Chen; Yuankui Sun; Xiaohong Guan (Water Research, 2023)

Green polyaspartic acid as a novel permanganate activator for enhanced degradation of organic contaminants: Role of reactive Mn(III) species - Yanghai Yu; Tiansheng Chen; Xiaohong Guan; Hongyu Dong; Junlian Qiao (Journal of Hazardous Materials, 2023)

Identification of the spatial patterns and controlling factors of Se in soil and rice in Guangxi through hot spot analysis - Xu Liu; Chaosheng Zhang; Tao Yu; Wenbing Ji; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Bo Li; Lei Wang; Yuxiang Shao; Kun Lin; Xudong Ma; et al. (Environmental Geochemistry and Health, 2023)

Identification of high ecological risk areas with naturally high background value of soil Cd related to carbonate rocks - Xu Liu; Tao Yu; Chaosheng Zhang; Cheng Li; Bo Li; Zhongfang Yang; Qiong Yang; Yiren Duan; Wenbing Ji; Tiansheng Wu; Lei Wang (Environmental Geochemistry and Health, 2023)

Natural variation of the BRD2 allele affects plant height and grain size in rice - Jinpeng Huang; Zhiming Chen; Jiajia Lin; Jinwen Chen; Menghao Wei; Liang Liu; Feng Yu; Zesen Zhang; Fangyu Chen; Liangrong Jiang; Jingsheng Zheng; Tiansheng Wang; et al. (Planta, 2022)

Potential Ecological Risk Assessment of Heavy Metals in the Fe–Mn Nodules in the Karst Area of Guangxi, Southwest China - Wenbing Ji; Zhongfang Yang; Tao Yu; Qiong Yang; Yubo Wen; Tiansheng Wu (Bulletin of Environmental Contamination and Toxicology, 2021)

Effect of cytochrome P450 2C19 polymorphisms on the clinical outcomes of voriconazole: a systematic review and meta-analysis - Xiaofei Li; Caiyuan Yu; Tiansheng Wang; Ken Chen; Suodi Zhai; Huilin Tang (European Journal of Clinical Pharmacology, 2016)